ANALYSIS OF CUSTOMER SATISFACTION LEVEL USING QFD AND IPA METHODS TO IMPROVE SERVICE QUALITY - Iil Nur Khamilatul Fitria; Wiwik Sulistiyowati (Antis Publisher, 2025)
Objective: The high level of complaints about service in the last three months—29.2% in September, 35.2% in October, and 35.2% in November—motivates this research to analyze the factors influencing the level of customer satisfaction at Gym Fitness Of Sidoarjo. Method: Data analysis was conducted by distributing questionnaires, which were then tested for validity and reliability. The analysis methods used are Quality Function Deployment (QFD) and Important Performance Analysis (IPA), which clarify how improvements can be made. Result: The research results reveal that the service variables in the dimensions of reliability and satisfaction that do not meet customer expectations include: workers providing wholehearted service, workers maintaining the cleanliness and comfort of the gym room, equipping gym equipment and repairing damaged facilities and infrastructure, and providing a suggestion box. Novelty: These findings suggest that improvements in these service areas can increase customer satisfaction and help maintain customer loyalty at Gym Fitness of Sidoarjo.